2006
DOI: 10.1007/s00126-005-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, geochemistry, and Nd isotope composition of the Rainbow hydrothermal field, Mid-Atlantic Ridge

Abstract: Petrological, geochemical and Nd-isotopic analyses have been carried out on rock samples from the Rainbow vent field to assess the evolution of the hydrothermal system. The Rainbow vent field is an ultramafic-hosted hydrothermal system located on the Mid-Atlantic Ridge, characterized by vigorous high-temperature venting (~365ºC) and unique chemical composition of fluids: high chlorinity, low pH and very high Fe and REE contents (Douville et al. 2002). Serpentinisation has occurred under a low-temperature (<270… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 72 publications
9
70
1
4
Order By: Relevance
“…It has been demonstrated that the REE patterns in these sulfides resemble the patterns of the hydrothermal fluids (Mills and Elderfield, 1995). Marques et al (2006) also demonstrated that REE patterns of sulfides from the Rainbow hydrothermal field, Mid-Atlantic Ridge clearly reflect the vent fluid REE pattern with significant LREE enrichment and positive Eu anomaly.…”
Section: Rare Earth Elements and Y Systematics Of Sulfidesmentioning
confidence: 80%
“…It has been demonstrated that the REE patterns in these sulfides resemble the patterns of the hydrothermal fluids (Mills and Elderfield, 1995). Marques et al (2006) also demonstrated that REE patterns of sulfides from the Rainbow hydrothermal field, Mid-Atlantic Ridge clearly reflect the vent fluid REE pattern with significant LREE enrichment and positive Eu anomaly.…”
Section: Rare Earth Elements and Y Systematics Of Sulfidesmentioning
confidence: 80%
“…Rainbow than at Logatchev (Douville et al 2002, Marques et al 2006. Moreover, 471 geochemical differences have been reported between black smokers within the Logatchev 472 field, mostly related to subsurface mixing with seawater, which results in cooling and 473 chemical alteration of the fluids emanating from some of the chimneys (Schmidt et al 474 2006).…”
Section: Microorganisms 438mentioning
confidence: 99%
“…Pyrite with Co/Ni > 1 has been used to distinguish pyrite of volcanogenic origin (e.g., Bralia et al 1979;Marques et al 2006), in particular where high-salinity brines interacted with volcanic host rocks. For example, Cl-rich fluids, which have Co/Ni > 1 (Douville et al 2002), are thought to have formed volcanogenic pyrite that is also distinguished by Co/Ni > 1 (Marques et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cl-rich fluids, which have Co/Ni > 1 (Douville et al 2002), are thought to have formed volcanogenic pyrite that is also distinguished by Co/Ni > 1 (Marques et al 2006). Similarly, Pal et al (2011) have argued that the chemical composition of their hydrothermal pyrite, which is enriched in Co with Co/Ni > 1, fingerprints a high-salinity fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation